2018
DOI: 10.1016/j.gca.2018.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of molybdenum in the continental crust

Abstract: The use of molybdenum as a quantitative paleo-atmosphere redox sensor is predicated on the assumption that Mo is hosted in sulfides in the upper continental crust (UCC). This assumption is tested here by determining the mineralogical hosts of Mo in typical Archean, Proterozoic, and Phanerozoic upper crustal igneous rocks, spanning a compositional range from basalt to granite. Common igneous sulfides such as pyrite and chalcopyrite contain very little Mo (commonly below detection limits of around 10 ng/g) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…Prior to the oceans, decoupling of Mo-W can be traced across estuaries where Mo behaves more conservatively than W (van der Sloot et al 1985, Bauer et al 2018 as well as into terrestrial environments as indicated by river waters with Mo/W ratios ranging from 0.3-68 (Mohajerin et al 2016, Bauer et al 2018. Terrestrial fractionation appears to begin in weathering profiles, but relative Mo-W mobility is probably controlled initially by protolith mineralogy (Greaney et al 2018) as evident by preferential W>Mo release recorded in a basaltic saprolite . The details of pedogenic Mo-W fractionation are poorly understood.…”
Section: Terrestrial Fractionation Of Th/u and Mo/wmentioning
confidence: 99%
“…Prior to the oceans, decoupling of Mo-W can be traced across estuaries where Mo behaves more conservatively than W (van der Sloot et al 1985, Bauer et al 2018 as well as into terrestrial environments as indicated by river waters with Mo/W ratios ranging from 0.3-68 (Mohajerin et al 2016, Bauer et al 2018. Terrestrial fractionation appears to begin in weathering profiles, but relative Mo-W mobility is probably controlled initially by protolith mineralogy (Greaney et al 2018) as evident by preferential W>Mo release recorded in a basaltic saprolite . The details of pedogenic Mo-W fractionation are poorly understood.…”
Section: Terrestrial Fractionation Of Th/u and Mo/wmentioning
confidence: 99%
“…In contrast, a lack of Mo isotope fractionation was observed in the dry Hekla volcanic rocks and less differentiated MORB (Bezard et al, 2016; Yang et al, 2015). Molybdenum is reported to be mainly hosted in rutile, titanite, iron oxides, amphibole, and biotite, occupying the octahedral site by replacing Ti 4+ , Fe 3+ , Nb 5+ , and Ta 5+ (Adam & Green, 2006; Bali et al, 2012; Greaney et al, 2018). Conversely, Mo coordination in silicate melts is predominantly tetrahedral, indicating that silicate minerals should favor the lighter Mo isotopes (Willbold & Elliott, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers envision only a minor influence of mantle (SCLM) sulfides on the bulk Mo budget due to the relatively low Mo contents and small proportion of sulfides (Wang & Becker, 2018). Nevertheless, the Mo contents in sulfides or sulfidic liquid can be quite heterogeneous (0.05–250 ppm; Greaney et al, 2018; Voegelin et al, 2012). The proportion of sulfides in the mantle may also be heterogeneous, because they are likely to aggregate or pond in the form of monosulfide solid solution or sulfide liquid (Liang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of rare accessory minerals including molybdenite and wulfenite has also been identified in a separate thesis [35]. It is suggested that molybdenite mineralization in this sample occurred due to the hydrothermal input of Mo and S. EPMA of the remaining phases indicate that molybdenite is the main Mo-bearing phase in this sample, but feldspars and muscovite contain MoO 3 concentrations in the range of the detection limit (0.06 wt %) which is 300 times more than the 0.2 mg/kg given by [36]. Interestingly, in another study of the same material wulfenite (PbMoO 4 ) was also found [35].…”
Section: Mineralogical Compositionmentioning
confidence: 57%